The Development of Emotional Intelligent Enhancing Program for Female Prisoners with Buddhist Teaching - Yunirum, Danaiphat; Wongsaparn, Onjira; Ruabthongsri, Suwaree; Boonprakob, Pannee (Journal of Behavioral Science for Development, 2023)
The objective of this research was to design and evaluate the results of Emotional Intelligent (EI) Enhancing Program and studied the effect of the program to thinking process and behaviors of female prisoners. This research conducted with a mixed research methodology; first stage was a quantitative study to design a program to enhance EI of female prisoners. Pre-test and Post-test were conducted with following up the results after 48 days of the program. The sample group were 292 female prisoners from Phitsanulok Women Correctional Institution. At the second stage, a qualitative study was conducted by in-depth interview 9 participants to study an effect of program against the prisoners’ thinking process and behaviors. The results of first stage have shown that the average post-test score was higher than pre-test at the 0.05 level of significance in all aspects. While the score of post-test and follow up-test did not have significant differences in all aspects except decision making and problem-solving ability aspect which was significantly higher in follow up test than post-test at the 0.05 level of significance. Moreover, it was found that 77.05% of participants (225 persons) had continued to practice mindfulness more than one time per week. The results of second stage shown that participants had considerably improved their thinking process and behaviors in all aspects. They were more calm, able to tackle their current situations constructively and live lives more peacefully.